2019
DOI: 10.1038/s41467-019-11813-6
|View full text |Cite
|
Sign up to set email alerts
|

Impaired mitochondrial calcium efflux contributes to disease progression in models of Alzheimer’s disease

Abstract: Impairments in neuronal intracellular calcium (i Ca 2+) handling may contribute to Alzheimer's disease (AD) development. Metabolic dysfunction and progressive neuronal loss are associated with AD progression, and mitochondrial calcium (m Ca 2+) signaling is a key regulator of both of these processes. Here, we report remodeling of the m Ca 2+ exchange machinery in the prefrontal cortex of individuals with AD. In the 3xTg-AD mouse model impaired m Ca 2+ efflux capacity precedes neuropathology. Neuronal deletion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
220
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 253 publications
(236 citation statements)
references
References 70 publications
13
220
3
Order By: Relevance
“…Despite the lack of expected premature neurodegeneration in the STIM2/ORAI1 mice, our novel model can be a useful tool for further studies of the role of SOCE proteins in neurons. This is especially relevant in the context of conflicting evidence of STIM2 actions in neuronal pathophysiology [10,31,33,[48][49][50][51][52], the involvement of ORAI1 in neurotransmission [53] and the growing body of evidence that links Ca 2+ homeostasis to AD-related neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite the lack of expected premature neurodegeneration in the STIM2/ORAI1 mice, our novel model can be a useful tool for further studies of the role of SOCE proteins in neurons. This is especially relevant in the context of conflicting evidence of STIM2 actions in neuronal pathophysiology [10,31,33,[48][49][50][51][52], the involvement of ORAI1 in neurotransmission [53] and the growing body of evidence that links Ca 2+ homeostasis to AD-related neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Recent results by Jadiya and colleagues demonstrate that neuronal deletion of the mitochondrial Na + /Ca 2+ exchanger in 3xTg-AD mutant mice (NCLX, Slc8b1 gene) accelerated memory decline and increased amyloidosis and tau pathology [31]. The downregulation of NCLX protein levels was also observed in postmortem brain of patients with non-familial, sporadic AD.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…In vivo experiments have shown that Aβ plaque deposition promotes Ca 2+ overload and calcineurin activation, which leads to downstream synaptic and dendritic spine pathology (Kuchibhotla et al, 2008;Wu et al, 2010). Age-dependent alterations in mitochondrial Ca 2+ efflux accelerate memory deficits and increase both amyloidosis and tau hyperphosphorylation in 3xTg-AD mice (Jadiya et al, 2019). Rescue of the expression of NCLX (a critical component of the mitochondrial Na + /Ca 2+ exchange) in these mice restored cognitive function and attenuated hippocampal neuronal degeneration.…”
Section: Editorial On the Research Topic Mitochondrial Dysfunction Anmentioning
confidence: 99%